Dissociative recombination cross section and branching ratios of protonated dimethyl disulfide and N-methylacetamide - al-Khalili, A; Thomas, R; Ehlerding, A; Hellberg, F; Geppert, W D; Zhaunerchyk, V; af Ugglas, M; Larsson, M; Uggerud, E; Vedde, J; Adlhart, C; Semaniak, J; et al. (The Journal of chemical physics, 2004)
Dimethyl disulfide (DMDS) and N-methylacetamide are two first choice model systems that represent the disulfide bridge bonding and the peptide bonding in proteins. These molecules are therefore suitable for investigation of the mechanisms involved when proteins fragment under electron capture dissociation (ECD). The dissociative recombination cross sections for both protonated DMDS and protonated N-methylacetamide were determined at electron energies ranging from 0.001 to 0.3 eV. Also, the branching ratios at 0 eV center-of-mass collision energy were determined. The present results give support for the indirect mechanism of ECD, where free hydrogen atoms produced in the initial fragmentation step induce further decomposition. We suggest that both indirect and direct dissociations play a role in ECD.